Alternatives to animal-derived extracellular matrix hydrogels? An explorative study with HepaRG cells in animal-free hydrogels under static and dynamic culture conditions - Nitsche, Katharina S.; Carmichael, Paul L.; Malcomber, Sophie; Müller, Iris; Bouwmeester, Hans (Frontiers in Toxicology, 2025)
New approach methodologies (NAMs) aim for animal-free chemical risk assessments. However, many in vitro NAM models still depend heavily on Matrigel and collagen despite the ethical, reproducibility, and biomedical concerns regarding the use of animal-derived materials. As awareness regarding this problem grows, several animal-free extracellular matrix hydrogel alternatives have emerged in the market. However, NAM studies with alternative hydrogels are rather scarce. The present study provides a concise review of commercially available animal-free hydrogels as well as an experimental screening approach to identify biocompatible candidates for HepaRG cell culturing under static and dynamic conditions in a 96-well plate and an OrganoPlate 3-lane device (Mimetas B.V.), respectively. The hydrogels evaluated herein include PeptiMatrix Core and PuraMatrix as synthetic peptides, VitroGel Organoid-3 as a synthetic polysaccharide, GrowDex as a wood-derived polysaccharide, and a Matrigel-collagen mix as the animal-derived reference. The health and functionality of the HepaRG cells were assessed via viability, lactate dehydrogenase leakage, albumin and bile acid secretion, CYP3A4 enzyme activity, and gene expression analyses. All animal-free hydrogels tested herein supported HepaRG cell proliferation in both culture conditions, although the cells had inadequate structure support and exhibited lower hepatic synthetic capacity in the OrganoPlate microphysiological system device. Notably, the cells grown in PeptiMatrix 7.5 showed promising metabolic competence under perfusion, making it a potential candidate for xenobiotic metabolism studies after further optimisation. These findings serve as a starting point to encourage scientists to take steps towards more animal-free cell culturing.